2016
DOI: 10.1001/jama.2016.5898
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neighborhood Walkability With Change in Overweight, Obesity, and Diabetes

Abstract: and diabetes have increased substantially in recent decades; however, the potential role of the built environment in mitigating these trends is unclear. OBJECTIVE To examine whether walkable urban neighborhoods are associated with a slower increase in overweight, obesity, and diabetes than less walkable ones. DESIGN, SETTING, AND PARTICIPANTS Time-series analysis (2001-2012) using annual provincial health care (N ≈ 3 million per year) and biennial Canadian Community Health Survey (N ≈ 5500 per cycle) data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
233
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 292 publications
(254 citation statements)
references
References 32 publications
5
233
1
8
Order By: Relevance
“…Increasing our understanding of the mechanisms through which the physical and social neighbourhood environment may influence body weight and obesity is crucial to effectively combat the current obesity epidemic [4]. There is some evidence that physical neighbourhood environmental characteristics such as limited access to sidewalks [5, 6], low aesthetics [5], low walkability areas [7, 8], larger distance to recreational facilities [6, 9] and higher fast food density [10, 11] are linked to higher body weights and obesity [12, 13]. Conversely, one longitudinal study conducted in Canada found that higher neighbourhood walkability was associated with lower prevalence of overweight and obesity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing our understanding of the mechanisms through which the physical and social neighbourhood environment may influence body weight and obesity is crucial to effectively combat the current obesity epidemic [4]. There is some evidence that physical neighbourhood environmental characteristics such as limited access to sidewalks [5, 6], low aesthetics [5], low walkability areas [7, 8], larger distance to recreational facilities [6, 9] and higher fast food density [10, 11] are linked to higher body weights and obesity [12, 13]. Conversely, one longitudinal study conducted in Canada found that higher neighbourhood walkability was associated with lower prevalence of overweight and obesity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Walkability indexes are measures of neighborhood characteristics that are conducive of higher levels of physical activity; these metrics have been found to be surrogate markers of physical activity levels and associated with health outcomes in the general population [10-13, 18, 19]. The Walk Score® (WS; www.walkscore.com) is a publicly available index of neighborhood characteristics that are conducive to walking in the United States, Canada, and Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Where possible, public health officers can work with local governments and planners when new developments or neighbourhood renewals are proposed to ensure land use planning facilitates active transportation, such as walking or biking, as studies have shown that walkability is linked to lower rates of diabetes and obesity (Creatore et al, 2016). Additionally, public health officials can encourage prioritization of such enhancement projects for low-socioeconomic status areas (BC Centre for Disease Control, 2017), as people in those neighbourhoods are likely to have a higher risk of chronic conditions, including diabetes (Novo Nordisk, 2015;University of British Columbia et al, 2015).…”
Section: The Role Of Public Health Practitioners In T2d Interventionsmentioning
confidence: 99%